SOCIAL AND PEDAGOGICAL FUNDAMENTALS OF SOCIAL SPHERE WORKERS’ TRAINING TO WORK WITH MIGRANTS IN SWEDEN - Popova, Anastasia (Studies in Comparative Education, 2017)
The article reveals social and pedagogical fundamentals of social sphere workers’ training for work with migrants in Sweden. The author has investigated the migration processes which take place in Sweden and which have become one of the features of the wealthy state development and formation of training the caseworkers. They are the specialists of the new generation, who are able to work with different ethnic groups and communities in terms of multiculturalism. The author has characterized and analyzed the main factors which influence the development and constant improvement of educational system for training social sphere specialists. It has been defined, that social and innovative educational policy of the Swedish state, the development of volunteer movement, functioning of organizations and associations of professional orientation have a significant role in the affirmation of the institute of social sphere workers. In the context of positive experience of implementation of social work system organization and social sphere workers’ training to work with migrants in Ukraine the author has proposed to pay attention at the adoption of corresponding legislative acts, which support and encourage migrants’ integration, prevent and obstruct their discrimination. It is also important to take into consideration the training of specialists, who work with this category of population; development of the integration policy and efficient system of social insurance, realization concerning the state and social projects of migrants’ support; creation of the branching network of the state and non-state centers, which encourage realization of integration policy.